2016
DOI: 10.1364/oe.24.025697
|View full text |Cite
|
Sign up to set email alerts
|

Infrared glass-based negative-curvature anti-resonant fibers fabricated through extrusion

Abstract: Negative curvature fibers have been gaining attention as fibers for high power infrared light. Currently, these fibers have been made of silica glass and infrared glasses solely through stack and draw. Infrared glasses' lower softening point presents the opportunity to perform low-temperature processing methods such as direct extrusion of pre-forms. We demonstrate an infrared-glass based negative curvature fiber fabricated through extrusion. The fiber shows record low losses in 9.75 - 10.5 µm range (which over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 21 publications
0
42
0
1
Order By: Relevance
“…This type of hollow-core fiber (HCF), referred to as hollow-core negative curvature fiber (NCF) in this paper (or more broadly named hollow-core anti-resonant fiber (ARF)) shows similar level of transmission loss and single modeness with the maturely developed hollow-core photonic-bandgap fiber (PBGF) and outperforms the PBGF in terms of broadband light guidance and high laser damage threshold. It has found plenty of interdisciplinary applications in areas ranging from ultra-intense pulse delivery [8,9], single-cycle pulse generation [10,11], low latency optical communication [5], UV light sources [12,13], mid-IR gas lasers [14] to biochemical sensing [15,16], quantum optics [17] and mid-IR to Terahertz waveguides [18,19]. In some of these applications, NCF has the potential to revolutionize the research field by realizing unprecedented performances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This type of hollow-core fiber (HCF), referred to as hollow-core negative curvature fiber (NCF) in this paper (or more broadly named hollow-core anti-resonant fiber (ARF)) shows similar level of transmission loss and single modeness with the maturely developed hollow-core photonic-bandgap fiber (PBGF) and outperforms the PBGF in terms of broadband light guidance and high laser damage threshold. It has found plenty of interdisciplinary applications in areas ranging from ultra-intense pulse delivery [8,9], single-cycle pulse generation [10,11], low latency optical communication [5], UV light sources [12,13], mid-IR gas lasers [14] to biochemical sensing [15,16], quantum optics [17] and mid-IR to Terahertz waveguides [18,19]. In some of these applications, NCF has the potential to revolutionize the research field by realizing unprecedented performances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows such a dependence for silica glass without taking into account the absorption of silica glass (line 1) and taking into account the absorption in the silica glass, provided that the wavelength corresponds to the center of the "zero" (line 2) and "second" (line 3) transmission band. The comparison of these lines shows that material losses can be neglected at short wavelengths only, but at wavelengths above ~4.7 μm they increase the total optical losses to the values above 1 dB/m (as was noted in [13].) Figure 4 also shows the analogous dependence for RF made of chalcogenide glass (line 5).…”
Section: Rf Design Optimization Based On Analytical Modelsmentioning
confidence: 60%
“…The first 6-rings of holes, hollow-core fiber, obtained in 2010 did not permitted any light propagation [13]. Later, A. Kosolapov et al [14], and R. Gattas et al [15] demonstrated light guidance beyond 10 μm through a Te-As-Se glass hollow-core fiber, and through an As-S hollow-core fiber respectively.…”
Section: Fiber Designs For Mid-infrared-guidingmentioning
confidence: 99%